The new yearbook for phenomenology and phenomenological philosophy. XII-12 - Hopkins, Burt C.; Drummond, John J., 1945-; Cambridge eBooks (Durham : Acumen Publishing, 2013)
The New Yearbook for Phenomonology and Phenomenological Philosophy provides an international forum for the latest research into the phenomenological tradition. This volume contains original research on the work of Husserl, Heidegger, Scheler, Levinas, Merleau-Ponty and Gadamer.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Phenomenology; Electronic books